Kualitas Penyelenggaraan Pelayanan Kartu Tanda Penduduk (KTP) Elektronik Melalui Unit Pelaksana Teknis (Upt) Dispendukcapil Kecamatan Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pasuruan - Subihandoko, Randika Didik (Jurnal Ilmiah Administrasi Publik, 2017)
This research aims to examine quality of services in the issuance of Electronic Identity Card (KTP) at Pasuruan District Agency of Population and Civil Registry Services. Qualitative method with descriptive research was used by conducting in- depth interviews to 50 users of card services Electronic Identity Card (KTP) that conducts electronic subscription card (KTP) application through the Technical Implementation Unit (UPT) of the Department of Population and Civil Registration of Sub-District. The results show the Quality of Implementation of Electronic Identity Card (KTP) services ranging from how the public knows the information electronic identity card (KTP) service mechanism, procedures and mechanisms of making or issuing electronic ID Card (KTP) , All of which are through the Technical Implementation Unit (UPT) of the Department of Population and Civil Registration of the Kecamatan.